2016
DOI: 10.18632/oncotarget.11073
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DR5 transport through disruption of lysosomal function suggests a novel mechanism for receptor activation

Abstract: To examine reciprocal or unilateral implications between two cell destruction processes, autophagy and apoptosis, in 5-Fluorouracil (5-FU)-treated tumor cells, a combination of chemical inhibitors, RNAi and genetic approaches were used. In contrast to cancer cells harboring obstructed apoptosis, either at the DISC or the mitochondrial level, p53-deficiency generated signs of autophagy deregulation upon chemotherapy. On the other, hand disruption of lysosomal function by chloroquine, caused a profound decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…7 ). In agreement with our findings, another recent study also reported that CQ induced cytoplasmic localization of DR5 and did not modulate TRAIL-induced apoptosis in human colon cancer HCT116 cells 38 . Moreover lysosome inhibition induced an additional isoform of DR5 protein smaller than 40 kD (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…7 ). In agreement with our findings, another recent study also reported that CQ induced cytoplasmic localization of DR5 and did not modulate TRAIL-induced apoptosis in human colon cancer HCT116 cells 38 . Moreover lysosome inhibition induced an additional isoform of DR5 protein smaller than 40 kD (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, co-localization studies showed higher levels of DR5 and LAMP-1 double-positive vesicles in HTNV-infected compared to uninfected cells ( Figures 7B, 7C, and S6). Chloroquine (CQ) has been shown to induce DR5 accumulation in lysosomes (Akpinar et al, 2016). Mirroring observations in HTNV-infected cells, perinuclear accumulation of DR5 and increased levels of DR5 and LAMP-1 double-positive vesicles were observed in CQ-treated uninfected cells ( Figures 7B and 7C).…”
Section: Htnv Infection Causes a Later Subcellular Relocalization Of Dr5mentioning
confidence: 61%
“… 5–8 Studies have also shown that TRAIL DR5 can trigger autophagy-related pathways and cause cell death. 9–12 …”
Section: Introductionmentioning
confidence: 99%